Human foot muscles strength and its association with acceleration sprinting, cutting and jumping performance kinetics in high-level athletes - Tourillon, R.; Michel, A.; Edouard, P.; Fourchet, F.; Morin, J. B. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The human foot is composed of intrinsic and extrinsic foot muscles that dissipate and generate net center of mass energy during rapid tasks such as running, jumping or hopping. In addition, it acts also as an efficacious lever during propulsion allowing rapid transfer of ankle plantar flexors forces into the ground. If this energetic and biomechanical role is indisputable, the literature pertaining to the relation between human foot muscles strength and sport performance is not well established. Therefore, the main aim of this study was to understand the relationship between metatarsophalangeal joint (MTPj) flexion strength and sprint acceleration, cutting and jumping performance and kinetics.